Against fixity : a hybrid reading of Breyten Breytenbach's art, poetry, writing, aesthetics and philosphy - Duffey, Alexander Edward (University of Pretoria, 2013)
Thesis (DPhil (History of Art))--University of Pretoria, 2008.